Maroon choreography - Ife, Fahima, 1983- (Black outdoors., 2021)
"In three long-form poems and a lyrical essay, Fahima Ife speculates on the afterlives of Black fugitivity, unsettling the historic knowledge of it while moving inside the ongoing afterlives of those people who disappeared themselves into rural spaces beyond the reach of slavery."--